Epidemiological changes of acute/recent human immunodeficiency virus type 1 infection in Barcelona, Spain (1997–2015): a prospective cohort study. (July 2019) - Nicolás, D.; Ambrosioni, J.; de Lazzari, E.; Suarez, A.; Manzardo, C.; Agüero, F.; Mosquera, M.M.; Costa, J.; Ligero, C.; Marcos, M.Á.; Sánchez-Palomino, S.; Fernández, E.; et al.
Abstract: Objective: To describe the epidemiology of acute/recent human immunodeficiency virus (HIV) infection over two decades in Barcelona (Spain). Methods: Prospective, single-centre cohort including all patients with an acute/recent HIV infection (<180 days) since 1997. Patients were stratified into four periods. Phylogenetic analysis was performed to determine clusters of transmission. Results: A total of 346 consecutive acute/recently infected patients were included. The annual proportion of recent infections among total new HIV diagnoses increased over time from 1% (29 out of 1964) to 8% (112 out of 1474) (p <0.001). Proportion of men who have sex with men (MSM) in the cohort increased from 62% (18 out of 29) to 89% (100 out of 112) (p <0.001). The proportion of migrants showed a non-significant increasing trend (24% (7 of 29) to 40% (45 of 112)) likewise the non-B subtype (0% to 22% (22 of 112)). The mean time from infection to diagnosis was 53.6 days (interquartile range (IQR) 50–57), comparable among all periods. Mean time from infection to treatment decreased over the years from 575 (IQR 467–683) to 471 (IQR 394–549) days (p <0.001) without significant differences between migrants and non-migrants (133 (IQR 71–411) versus 208 (IQR 90–523) days p 0.089). Almost 50% (152 of 311) of recently infected individuals were included in a cluster of transmission, and 92% (137 of 149) of them were MSM. Conclusion: The MSM population has progressively grown within acutely/recently infected patients in Barcelona, and is frequently involved in transmission clusters. Although the time between diagnosis and treatment has been reduced, the time between infection and diagnosis still needs to be shortened.